2017
DOI: 10.1055/s-0037-1604102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magill Forceps to Remove Foreign Bodies in Children

Abstract: Accidental foreign body (FB) ingestion is a common clinical problem.1 FB ingestion is highly prevalent among the pediatric age group. In adults, it occurs most frequently in alcoholics, prisoners, and those with mental retardation. 2,3Radiological localization of ingested FB using advanced techniques is mandatory. 4 Esophagoscopy is the main method for the removal of FBs. Rigid esophagoscopy has been mainly associated with a 5 and 10% risk of perforation during FB removal. The ideal methods are all of the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…However, no clear recommendations on endotracheal intubation or other details are available. 15,18 Only two statements on the issue of anesthesia appear to be significant: It should be provided as fast as possible and by an anesthetist with pediatric expertise. 10 As we deliberately did not define a standardized anesthesia technique regarding drugs used and the instrumentation of the airway, we observed that in one center, general anesthesia was never accompanied by endotracheal intubation or usage of a neuromuscular blocking agent.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear recommendations on endotracheal intubation or other details are available. 15,18 Only two statements on the issue of anesthesia appear to be significant: It should be provided as fast as possible and by an anesthetist with pediatric expertise. 10 As we deliberately did not define a standardized anesthesia technique regarding drugs used and the instrumentation of the airway, we observed that in one center, general anesthesia was never accompanied by endotracheal intubation or usage of a neuromuscular blocking agent.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the ENT team made a poor management decision at the time. However, a perforation induced by Magill forceps is exceptional [1,2,6]. Some ENT teams are used to extract foreign bodies from the cervical esophagus using Magill's forceps with great success and little or no complication [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, a perforation induced by Magill forceps is exceptional [1,2,6]. Some ENT teams are used to extract foreign bodies from the cervical esophagus using Magill's forceps with great success and little or no complication [6]. The average of delay diagnosis for esophageal iatrogenic perforations in infants is 1.4 days (0-2 days) [7].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of therapeutic procedures to remove esophageal foreign bodies has been described. These include flexible and rigid endoscopy, Foley catheter extraction, bougienage, and the use of Magill forceps [9,10,11]. Flexible endoscopy under general anesthesia is the therapeutic procedure of choice because the foreign body can be directly removed and the esophagus can be examined for potential complications and other pathology [1].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 patients, 22 had ingested fish or poultry bones, and the rest had ingested glass or metal objects. In a recently published article, Turkish authors reported very good clinical experience in removal of different foreign bodies from proximal esophagus by Magill forceps in almost all of the 88 pediatric patients [11].…”
Section: Discussionmentioning
confidence: 99%